Efeitos organizacionais da implantação de metas e remuneração variável por desempenho: o caso da segurança pública em Minas Gerais - Assis, Luis Otávio Milagres de (2012)
Which are the practical effects caused by the demand for goal achievement in institutions and public servants? And what about connecting financial rewards to this achievement, what is the result from that? Brazil has been experiencing an implementation wave of performancerelated pay systems in the public sector recently. The state of Minas Gerais universalized the system in 2008 by implementing The Results Agreement and the Productivity Award, having already spent more than 720 million dollars in the program. However, managers’ optimism does not find any basis in the theory. Literature shows that variable-pay systems in the public sector have failed or mildly succeeded (OCDE, 2005; Perry, Engbergs and Jun, 2009; Bowman, 2010; Weibel, Rost and Osterloh 2010). Many incentive experiences have been led to failure by conflicts, performance-measuring difficulties, fraud and lack of motivation ability over public servants. Some few studies show that under certain circumstances performance-related pay systems may bring positive results (Marsden, 2010). Would the system from Minas Gerais be capable of overcoming specialists’ pessimism and reaching positive outcomes? Which mechanisms in fact take place when there is an implementation of goals and variable payment in public institutions? This work aims to answer these questions by studying the case of three Public Safety organizations in Minas Gerais: Military Police, Investigation Police and Fire Department. 46 interviews with policemen, firemen and the top officers from the institutions were conducted, analyzing statistic data – which assess performance evolution, participant observation and the monitoring of the media perception towards these effects. The result shows that goals and financial incentives have created profound changes in the researched institutions. There were a productivity growth, control increase and internal procedures improvements in Investigation Police. However, the focus on quantitative production of police investigations incentivized their quality reduction. A minor impact was observed in the Military Police, since this institution had recently taken in gains which the usage of goals and performance indicators could provide. Nevertheless, an increase in the internal demand for results was observed. This was one of the factors which contributed to a negative, significant effect: crimes reclassification. An incentive structure and the absence of obstacles made it possible for some police officers to reclassify crimes which had similar nature in order to improve some of their departments’ statistics. In the Fire Department the impact was highly positive, taking the institution to conceive new strategies, generate important productivity gains and improve results of the services delivered to the citizens. The result shows that goals and financial incentives are very powerful and may cause positive or negative results, depending on the way they are implemented. Evidences are partly contradictory to the academic pessimism and reveal the functioning of the mechanisms which make goals and performance-related pay interfere with public organizations’ results.